Pengaruh POC NASA dan NUPOC terhadap Pertumbuhan Tanaman Talas Jepang (Colocasia esculenta var. antiquorum): The Effect of POC NASA and NUPOC on the Growth of Japanese Taro (Colocasia esculenta var. antiquorum) - Dewi, Afkarin Kamilah; Laili, Saimul; Tito, Sama' Iradat (Jurnal SAINS ALAMI (Known Nature), 2024)
Liquid organic fertilizer is a solution derived from the decomposition of plant residues, agro-industry, animal faeces, and humans and contains more than one nutrient. POC Nasa liquid organic fertilizer is mainly used for all types of food crops and perennial plants that contain micronutrients and are equivalent to one ton of manure. NUPOC is believed to increase plant vegetative and generative productivity, increase soil fertility, and make plants healthy and safe for the environment. Taro is classified as a taro (Araceae) that can grow in tropical and subtropical areas. This study aimed to study the effect of POC Nasa and NUPOC, as well as the optimum concentration on the growth and yield of Japanese Taro plants. This study was designed with a completely randomized design consisting of two factors. The first factor is POC, consisting of POC Nasa and NUPOC; the second is the concentration starting from the control, 5, 10, 15, and 20 ml/litre of water with three replications. Observations were made on plant height, area and number of leaves, dry and wet weight of leaves. ANOVA analysis for significant differences in each treatment was then continued with a 5% DMRT test, providing results that administration with a concentration of 10 ml/litre of POC Nasa and NUPOC showed a significant effect on all observation variables. Keywords: POC NASA, NUPOC, Japanese Taro ABSTRAK Pupuk organik cair merupakan larutan dari hasil dekomposisi residu tanaman, agroindustri, feses hewan, dan manusia dengan terkandung lebih dari satu unsur hara. Pupuk organik cair POC Nasa utamanya digunakan untuk semua jenis tanaman pangan dan tanaman tahunan yang mengandung mikronutrien dan setara satu ton pupuk kandang. Sedangkan NUPOC dipercaya dapat menaikkan produktivitas vegetative tanaman dan generatifnya, kesuburan tanah meningkat, menyehatkan tanaman serta aman bagi lingkungan. Talas tergolong keladi (Araceae) yang dapat tumbuh didaerah tropis maupun subtropis. Tujuan penelitian ini adalah untuk mempelajari pengaruh POC Nasa dan NUPOC, serta konsentrasi optimum pada pertumbuhan dan hasil tanaman Talas Jepang. Penelitian ini didesain dengan rancangan acak lengkap terdiri atas dua faktor. Faktor pertama adalah POC terdiri dari POC Nasa dan NUPOC, faktor kedua yaitu konsentrasi dimulai dari kontrol, 5, 10, 15, dan 20 ml/liter air dengan 3 kali ulangan. Pengamatan yang dilakukan pada tinggi tanaman, luas dan jumlah daun, berat kering, dan berat basah daun. Analisis ANOVA untuk adanya perbedaan yang nyata pada setiap perlakuan kemudian dilanjut uji DMRT 5%, memberikan hasil bahwa pemberian dengan konsentrasi 10 ml/liter POC Nasa dan NUPOC menunjukkan pengaruh nyata terhadap seluruh variabel pengamatan. Kata kunci: POC NASA, NUPOC, Talas Jepang